Use of guideline‐recommended adjuvant therapies and survival outcomes for people with colorectal cancer at tertiary referral hospitals in South Australia. Issue 1 (4th May 2017) - Adelson, Pamela; Fusco, Kellie; Karapetis, Christos; Wattchow, David; Joshi, Rohit; Price, Timothy; Sharplin, Greg; Roder, David
Abstract: Rationale, aims and objectives: Adjuvant care for colorectal cancer (CRC) has increased over the past 3 decades in South Australia (SA) in accordance with national treatment guidelines. This study explores the (1) receipt of adjuvant therapy for CRC in SA as related to national guideline recommendations, with a focus on stage C colon and stage B and C rectal cancer; (2) timing of these adjuvant therapies in relation to surgery; and (3) comparative survival outcomes. Methods: Data from the SA Clinical Cancer Registry from 4 tertiary referral hospitals for 2000 to 2010 were examined. Patterns of care were compared with treatment guidelines using multivariable logistic regression. Disease‐specific survivals were calculated by treatment pathway. Results: Four hundred forty‐three (60%) patients with stage C colon cancer and 363 (46%) with stage B and C rectal cancer received guideline‐recommended care. While an overall increase in proportion receiving adjuvant care was not evident across the study period, the proportion having neoadjuvant care increased substantially. Older age was an independent predictor of not receiving adjuvant care. Patients with stage C colon cancer who received recommended adjuvant care had a higher 5‐year survival than those not receiving this care, ie, 71.2% vs 53.2%. Similarly adjuvant therapy was associated with better outcomes for stage C rectal cancers. The median time for receiving adjuvant care was 8 weeks. Conclusions: Survival was better for stage C CRC treated according to guidelines. Adjuvant care should be provided except where clear contraindications present. Other possible contributors to guideline adherence warranting additional investigation include co‐morbidity status, multidisciplinary team involvement, and choice.